1992
DOI: 10.11150/kansenshogakuzasshi1970.66.914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gentiana Violet against Methicillin-Resistant Staphylococcus aureus (MRSA)

Abstract: The bactericidal effect of gentiana violet against MRSA isolated from clinical specimens was studied both in vitro and in vivo. The results obtained are as follows: 1) Minimum bactericidal concentration (MBC) of gentiana violet to MRSA was between 0.0025% and 0.08% and the MBC was not influenced even if 25% human whole serum exists in the medium. 2) The number of cells were 2.1 x 10(7) CFU/ml in medium which decreased to 5.4 x 10(4) CFU/ml within 5 min by existing 0.1% gentiana violet in the medium as the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…On the other hand, the observed necrotic lesions might not have been caused by the highdose steroid therapy, given that a similar lesion developed prior to steroid therapy in case 5, and reappeared in case 4 during a 5-mg daily dose of prednisolone. The present study confirmed the previously reported finding that topical bactericidal reagent gentiana violet reduces the risk of local infection with methicillin-resistant Staphylococcus aureus, 6 and further found that it accelerated the healing of the skin, as in case 4. Thus, strict sterilization is considered to be essential for treatment of this type of lesion.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the observed necrotic lesions might not have been caused by the highdose steroid therapy, given that a similar lesion developed prior to steroid therapy in case 5, and reappeared in case 4 during a 5-mg daily dose of prednisolone. The present study confirmed the previously reported finding that topical bactericidal reagent gentiana violet reduces the risk of local infection with methicillin-resistant Staphylococcus aureus, 6 and further found that it accelerated the healing of the skin, as in case 4. Thus, strict sterilization is considered to be essential for treatment of this type of lesion.…”
Section: Discussionsupporting
confidence: 92%
“…Recent laboratory data have suggested that gentian violet may be efficient against MRSA 5 . In addition, eradication of MRSA from decubitus ulcers with gentian violet has been reported 6 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been attracting attention as a local therapeutic agent for methicillin‐resistant Staphylococcus aureus . Therefore, in regard to carcinogenensis and toxicity, there may be no problem in terms of safety when crystal violet is used 22,23 …”
Section: Practice Of Pit Observation By Magnifying Endoscopymentioning
confidence: 99%
“…Therefore, in regard to carcinogenensis and toxicity, there may be no problem in terms of safety when crystal violet is used. 22,23 Digestive Endoscopy (2001) 13 (Suppl. ), S10-S13…”
mentioning
confidence: 99%